Estimation of Cosmological Constant of Nearby Spiral Galaxies using Rotation Curve - Bachhan, RK; Aryal, B; Khanal, U (Scientific World, 2010)
An expression for rotational velocity of a test particle around the central mass in the invariant plane is derived. For this, a line element of Schwarzschild de-Sitter space-time is used to study the effect of cosmological constant Λ) on the motion of both massive and mass-less particles in the Universe. This expression is fitted for the mass and Λ. For this, the total mass M is divided into the mass of the black hole MB and a uniform sphere of radius r dominated by dust (ρd) which is supposed to vary as [please see full text PDF for the formula]. Using rotation curve data of 6 nearby spiral and barred spiral galaxies, we estimated the value of Λ and the mass of the galaxy. The cosmological constant (Λ) is found to be positive for all 6 galaxies. The positive Λ reveals the importance of de Sitter space, suggesting accelerating Universe. The cosmological constant (Λ) and the density (ρo) are found to lie in the range 1.269 x 10-41 to 9.490 x 10-42 km-2, and 7.044 x 10-9 to 3.250 x 10-8 km-1, respectively. The mass MB is found in the range 1.867 x 107 to 1.730 x 1010 solar mass. Our result shows a good agreement with the results of supernova project which gives positive Λ value, suggesting accelerating Universe. Keywords: Galaxies formation; General astronomical databases. DOI: 10.3126/sw.v8i8.3840 Scientific World Vol.8(8) 2010 pp.15-18